A new status and combination in a Madagascan Kalanchoe, K. brevicalyx (Crassulaceae subfam. Kalanchooideae) - Smith, Gideon F.; Figueiredo, Estrela (Phytotaxa, 2020)
The proposed name at new rank ‘Kalanchoe brevicalyx’ (Raymond-Hamet & Perrier de la Bâthie 1915: 88) L.Allorge (in Boiteau & Allorge-Boiteau 1995: 133) (Crassulaceae subfam. Kalanchooideae) was not validly published as a full and direct reference to the place of valid publication of the basionym, K. pinnata var. brevicalyx Raymond-Hamet & Perrier de la Bâthie (1915: 88), with page or plate reference and date, was not clearly indicated (Turland et al. 2018: Art. 41.5). We here validly publish the new combination and status.